Pre season balance and jump landing training program and its effect upon female basketballers' static and dynamic balance and knee and ankle injury rates - Sampson, L. J. (2005)
The effect of a preseason conditioning program of balance and jump landing training exercises was studied to evaluate its influence on static and dynamic balance and the occurrence of ankle and knee injuries in Basketball. Fifty-eight female representative Basketball players (aged 9-17 years) were studied over one season. Twenty-nine of these players participated in a six week training program implemented during the preseason. Pre and post tests measured balance and injuries documented over one season. The experimental group`s static and dynamic balance improved significantly as measured by a stork stand test and a multiple single-leg hop-stabilisation test In a post hoc analysis of dynamic balance, participants in the 12-13 years experimental group performed significantly better on dynamic balance, whereas the 12-13 years control group performed poorest compared with all other age cohorts. The lower limb injury rate for the 29 experimental group participants was .78 injuries per 1 000 hours, while the control group sustained no lower limb injuries in the 2001 season, based on the injury definition utilised in the study. This finding was statistically significant although three of the four injuries sustained were contact injuries. The study findings indicate that appropriately defined balance training can be beneficial for improving balance ability in female Basketball players. Evidence was found in the study for the existence of a critical age when balance training should be introduced to maximise the benefit for young female adolescent Basketball players.